2014
DOI: 10.1111/sms.12284
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vertical jump and maximal power output of legs and arms: Effects of ethnicity and sport

Abstract: The hypothesis that ethnicity and sport practice influence the relationship between maximal power in cycling (P(max)) and countermovement jump (CMJ) has been studied by relating CMJ and P(max) in two groups (volleyball players, VB, and physical education students, PES) including subjects with Caucasian (67 C) or West African (39 WA) origins. Maximal power of the arms (P(max) Arms) was also measured. A two-way analysis of variance (groups × ethnicity) showed significant effects of both factors upon CMJ, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…Based on previous studies (Rouis et al, 2015), the results of the present study indicated that ethnicity significantly impacted the Pmax-VJ relationship. Indeed, the results of the multiple linear regression analysis showed that, for a given value of Pmax, the Afro-Caribbean participants jumped on average 8 cm higher than the Caucasians.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Based on previous studies (Rouis et al, 2015), the results of the present study indicated that ethnicity significantly impacted the Pmax-VJ relationship. Indeed, the results of the multiple linear regression analysis showed that, for a given value of Pmax, the Afro-Caribbean participants jumped on average 8 cm higher than the Caucasians.…”
Section: Discussionsupporting
confidence: 71%
“…However, a number of studies have highlighted that the Pmax-VJ relationship is impacted by ethnicity (Rouis et al, 2015). For example, for a given value of VJ, Pmax of West African volleyball players was lower than Pmax of their Caucasian counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The height (in meter; m) reached in a vertical jump is generally considered the gold standard of determining the muscular power of the lower extremities (Earp et al, 2010; Rouis et al, 2015) and is also an indicator of anaerobic fitness (Ostojić et al, 2010). In addition, jump height can provide information concerning the functional capacity of different populations (Amonette et al, 2012;Farias et al, 2013) and physical performance in several sports (Ziv and Lidor, 2010a;Ziv and Lidor, 2010b).…”
Section: Introductionmentioning
confidence: 99%